2021
DOI: 10.3390/jcm10020346
|View full text |Cite
|
Sign up to set email alerts
|

Association of NAFLD and Insulin Resistance with Non Metastatic Bladder Cancer Patients: A Cross-Sectional Retrospective Study

Abstract: Among risk factors (apart from smoking) likely involved in bladder cancer (BCa), metabolic syndrome (MS), obesity and type 2 diabetes mellitus (T2DM) have been explored with contrasting results. In spite of these studies, there is little data on the association between nonalcoholic fatty liver disease (NAFLD), its main driver, i.e., insulin resistance (IR), and BCa. Implanting a cross-sectional retrospective study we tried to investigate both NAFLD and IR prevalence in a hospital based population of BCa patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 47 publications
1
72
0
Order By: Relevance
“… 22 Tarantino et al reported the TyG index predicted NAFLD presence in bladder cancer. 23 However, those studies focused on this relationship only in specific populations. Another cross-sectional study compared TyG and HOMA-IR as predictors of the prevalence of NAFLD, reporting that TyG is superior to HOMA as a NAFLD predictor and is also related to the severity of NAFLD in Korean adults.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Tarantino et al reported the TyG index predicted NAFLD presence in bladder cancer. 23 However, those studies focused on this relationship only in specific populations. Another cross-sectional study compared TyG and HOMA-IR as predictors of the prevalence of NAFLD, reporting that TyG is superior to HOMA as a NAFLD predictor and is also related to the severity of NAFLD in Korean adults.…”
Section: Discussionmentioning
confidence: 99%
“…The De Ritis ratio was reported to be higher in patients with non-metastatic bladder cancer. [ 28 ] Furthermore, the De Ritis ratio has also been reported to be a significant prognostic indicator for testicular cancer, renal cell carcinoma, bladder cancer, pancreatic cancer, solid tumor, and oropharyngeal cancer [ 8 , 9 , 10 , 11 , 29 , 30 , 31 ]. In patients who have undergone radical cystectomy, an elevated De Ritis ratio is associated with overall survival and disease-specific survival [ 10 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These factors may increase the risk of BCa recurrence and lead to a poor prognosis (121). Studies have shown that patients with BCa had higher insulin resistance than those without cancer but with bladder disease (122). DM was associated with elevated BCa or cancer mortality risk, especially in men (123).…”
Section: Other Factors Affecting the Prognosis Of Bca Systemic Diseasesmentioning
confidence: 99%